Front cover: Large‐scale multiplex absolute protein quantification of drug‐metabolizing enzymes and transporters in human intestine, liver, and kidney microsomes by SWATH‐MS: Comparison with MRM/SRM and HR‐MRM/PRM. Issue 15 (August 2016) - Nakamura, Kenji; Hirayama‐Kurogi, Mio; Ito, Shingo; Kuno, Takuya; Yoneyama, Toshihiro; Obuchi, Wataru; Terasaki, Tetsuya; Ohtsuki, Sumio
Abstract : DOI:10.1002/pmic.201500433 Metabolizing enzymes and transporters are key molecules that function cooperatively to regulate the absorption, metabolism and excretion of medicinal drugs. Absolute protein levels of 30 metabolizing enzymes and 107 transporters were simultaneously quantified in microsomes of human liver, kidney and intestine by means of SWATH‐MS with stable isotope‐labeled peptides, and the results were compared with those obtained by MRM/SRM and high resolution‐MRM/PRM. For more details, see the article by Kenji Nakamura et al. on pages 2106–2117.